Food service management for senior high - Tan, Lawrence Li; de Guzman, Florentine Cabuyao (Mandaluyong City Anvil Publishing Inc., 2016)
Food service management equips the students with knowledge on: the food service industry, culinary skills and methods, the food and beverage service sequence, beverages and bar operation and restaurants service equipment. This book also includes insights from seasoned local and international industry.
Chapter 1: The Food service industry -- Chapter 2: Restaurant service equipment -- Chapter 3: The food and beverage service sequence -- Chapter 4: Bar and beverages -- Chapter 5: Culinary.
Includes bibliography (page 195).
Keywords: Food service management -- Study and teaching